PELATIHAN KADER TENTANG DETEKSI DINI GANGGUAN JIWA DI WILAYAH KERJA PUSKESMAS MARGAHAYU KOTA BANDUNG (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2023)
The prevalence of people with mental problems (ODMK) reaches 9.3 percent or around three million people. This high number is predicted to continue to increase due to the condition of the Covid 19 pandemic which creates new stressors for the community. so that currently we need cadres who are able to detect early mental disorders in the community so that preventive actions can be carried out immediately in the community. Increasing the ability of cadres to detect mental disorders early can be done through cadre training in the form of community service. The purpose of this community service is to find out the level of knowledge and attitudes of cadres before and after being given training on Early Detection of Mental Disorders (DDGJ). The community service method used is cadre training using the DDGJ module. The results of community service show that before being given cadre training, the mean knowledge was 48.48 and attitude was 64.02. after being given cadre training, it was found that the average value of knowledge increased was 80.30, the increase was 31.82, while the mean value of attitude was 88.86, an increase of 24.85. The conclusion of community service is that there is an increase in the knowledge and attitudes of cadres after training on early detection of mental disorders.